(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The natural factors represented by the geographical location of the study area showed the presence of four sediments in the Quaternary time, represented by floodplain deposits, depression-filling sediments, marsh sediments, and human-induced sediments. The surface of the area is relatively flat, and its height ranges between (20m) above sea level in the southeastern part and (53m) above sea level in the western part of the study area. The climate has an effect on the high temperature in the study area in the summer, which affects the amount of water resources, as its high increases evaporation. The rainfall in the study area is characterized by its winter nature, in which there is no rain during the summer months, and through that, we found an indicator that cannot be relied upon in supplying water resources to the study area, whether surface or groundwater, and the greatest dependence on the unified channel coming from the Euphrates River. And that the evaporation element is of great importance in the hydrological cycle, as evaporation affects the determination of the annual water revenue in quantity and quality, especially its impact on the quality and quantity of groundwater. There are (24) wells in the region, including civil wells that were dug by the residents of the region, and governmental wells that were dug by the General Authority for Ground Water, especially in (the period of scarcity), which is the period that witnessed the interruption of the water of the Unified Canal and the irrigation streams associated with it due to the actions of the terrorist ISIS . There are two types of soils in the study area according to Björnck’s classification, which are the soils of river basins buried in silt and the soils of river shoulders. The natural plants in the study area were classified into five types, namely, riverbank plants, marsh and swamp plants, agricultural field plants, depression plants, and ancient riverbed plants.Keywords: natural ingredients, Yusufiyah River, sediments, wells, plantsA research extracted from a letter: The Yusufiyah River and its investment in the Al-Rasheed district (a study in the geography of resources).